The Role Of Digital Marketing, Innovation, And Product Quality On The Performance Of UMKM In Batam City - Feryani; Wasiman (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study examines the role of digital marketing, innovation, and product quality on the performance of UMKM in Batam City as a strategic region adjacent to Singapore and Malaysia. The main problem is the low competitiveness of UMKM amid globalization, changing consumer behavior, and intense competition, despite the number of UMKM fostered by the Batam City Government reaching 1,748 units (April 2024). The research objectives are to test the partial and simultaneous effects of the three variables on UMKM performance. The method used is descriptive quantitative with a sample of 110 MSMEs in the Nagoya, Tembesi, and Sekupang areas, employing a 5-point Likert-based questionnaire and regression analysis via SPSS 21. The main results show that digital marketing (t=3.510; sig. 0.001), innovation, and product quality have a positive and significant partial effect; simultaneously (F-test), the three variables together enhance sales growth, customer base, and profits. The synthesis of findings reinforces that the synergy of these three factors creates sustainable competitive advantage. Conclusion: Batam UMKM must optimize digital platforms, continuously innovate, and maintain quality consistency to compete in the digital economy era. This research provides empirical contributions to UMKM development strategies in border regions.